(untitled) (Research, Society and Development, 2023)
The Eastern Brazilian Pegmatite Province (EBPP) constitutes a wide region located almost entirely at the eastern portion of the Minas Gerais State, where granitic rocks and associated pegmatites occur and commonly represent important mineral deposits. This mineral province encompasses pegmatite districts with peculiar features in geographic and geotectonic terms. Among them, the Santa Maria de Itabira District represents the most southerly and it’s not very well known in geologic terms; its economic relevance is related mainly to beryllium minerals as beryl (emerald and aquamarine) and chrysoberyl (alexandrite). This paper aims to describe and characterize the main mineralized areas in the district, from literature available and new geological data. Deposits are divided in three pegmatite fields designated Itabira–Nova Era, Santa Maria de Itabira–Hematita and Ferros–Esmeraldas de Ferros. The first one constitutes mainly an emeraldiferous belt of great economic potential, in which the most important deposits are those of Belmont, Piteiras and Capoeirana. The second pegmatite field (Santa Maria de Itabira–Hematita) presents pegmatites of economic importance for aquamarine production, emphasising Ponte da Raiz, Morro Escuro, Jatobá and Tatu deposits, nearby Santa Maria de Itabira, besides pegmatites producing alexandrite at Antônio Dias. The third field (Ferros–Esmeraldas de Ferros) has nowadays few mining activities, although have already produced giant topaz crystals, in addition to have been the site of first emerald discovery in Minas Gerais. The results obtained point to mineralogical peculiarity of the district in relation to other in the EBPP.